International strategy and analysis of feasibility report variables in the light of strategic alliance models - Çelik, Güneş (My University, 1999)
The main objective of this study is to analyse the variables that influence international strategies of the companies, especially by focusing to foreign direct investment models (FDI). In the first part, the definition, the reasons and the opportunities for developing an International Strategy; factors that influence these strategies; strategic alliance models and mode of entries; and keys to strategic alliances potential problems are explained. The above mentioned subjects are illustrated with different international applications (cases). In the second part, a feasibility study model's variables are presented, marketing and business assumptions and their impact on the financial results are explained. In the third part, by means of a feasibility model nine different investment scenarios are created with the help of a program that I developed on the excel. The financial results of the three basic FDI strategies;- foundation of a new subsidiary, acquisition of an existing company, and foundation of a JV with a local partner- are compared to support the statements given in the first part.

Bu çalışmanın asıl amacı, özellikle dogrudan yatırım modelerine odaklanarak, şirketlerin uluslararası stratejilerini belirlimede etkili degişkenlerin incelenmesidir. Birinci bölümde uluslararası stratejinin tanımı, nedenleri ve uluslararası strateji geliştirmenenin getirecegi fırsatlar, strateji geliştirmeye etkiyen faktörler, stratejik işbirligi modelleri, ve bu işbirligi modellerinin dogurması olası problemler ve çözüm yolları anlatılmıştır. Yukarıda belirtilen konular uluslararası uygulamalar ile örneklendirilmiştir. İkinci bölümde bir fizibilite çalışmasındaki degişkenler, pazar ve iş yapısı ile ilgili kabuller açıklanmış ve bunların finansal sonuçlara olan etkileri irdelenmiştir. Üçüncü bölümde excel'de oluşturdugum kullanarak bir fizibilite modeli yardımı ile dokuz degişik yatırım senaryosu yaratılmıştır. Bu senaryoların sonucunda elde edilen finansal sonuçlar, birinci bölümde üç temel dogrudan yatırım modeli -yeni bir şirket kurma, olan bir şirketi satın alma, ortaklık- ile ilgili belirtilenleri desteklemektedir.
Keywords: Ekonomi; Finansman ekonomisi; Yatırım; YATIRIMLAR-FİZİBİLİTE; YATIRIMLAR-STRATEJİ